Construction and calibration of weighing lysimeters with an automated drainage system - Sanches,Arthur C. (2017)
ABSTRACT Quantification of the drained volume is one of the difficulties involved in using weighing lysimeters. Typically, this volume is measured by accessing a moat at the base of a lysimeter. However, it is not feasible to install the moat in small devices. Thus, the aim of this study involves developing, installing, calibrating, and checking the efficiency of small weighing lysimeters with automated drainage systems to test their functionality in field conditions. Each lysimeter is composed of a round PVC water tank with a diameter of 1.22 m and a depth of 0.58 m that is placed over a metal frame with three electronic load cells with the nominal capacity of each cell corresponding to 500 kg. The drainage system is composed of a small reservoir with a volume of 10 L, a weighing structure composed of a load cell with a nominal capacity of 30 kg, and an automatic solenoid valve driven by a device coupled to a data logger that records the data from the lysimeter and from the drainage system. Two calibrations are performed for the lysimeter as well as the drainage system to obtain equations with significant correlations (R2 > 0.9999). The drainage system was activated several times during the tests after receiving approximately 63.4 L of water from rainfall, and this in turn indicated a good performance.